Effects of cyclic confining pressure on the deformation characteristics of natural soft clay. Issue 78 (November 2015) - Sun, Lei; Gu, Chuan; Wang, Peng
Abstract: To investigate the coupling effects of cyclic deviator stress and cyclic confining pressure on the deformation behavior of natural soft clay under partially-drained conditions, a series of one-way cyclic triaxial tests with and without cyclic confining pressure were carried out. Test results show that, at the same amplitude of cyclic deviator stress, the increase of cyclic confining pressure amplitude will accelerate the accumulation of both permanent volumetric and axial strain significantly. The comparison between test results for different amplitudes of cyclic confining pressure shows that tests with a cyclic confining pressure corresponding to a stress path of η ampl = p ampl / q ampl =1 lead to a 1.4 times larger permanent volumetric strain and a 1.2 times larger permanent axial strain compared to the conventional cyclic triaxial tests with constant confining pressure ( η ampl =1/3). In case of η ampl =2 the permanent strains are found to be even 2.0 or 1.5 times larger compared to the standard tests. Finally, an empirical formula is proposed for the prediction of permanent axial deformations of natural soft clays under partially-drained conditions, considering the effects of cyclic confining pressure. Highlights: The excess pore water pressure is influenced by cyclic confining pressure. The cyclic confining pressure accelerates the volumetric and axial strain accumulation. An empirical formula is proposed.